PEMBELAJARAN MATEMATIKA DALAM PENERAPAN SPLDV SOAL CERITA PADA PESERTA DIDIK KELAS X SMK MUHAMMADIYAH REMBANG - Endang Purgiyanti; Mochamad Akrom; Diah Rosi Kartika Sari; Suntari Suntari (Litbang PWM Jawa Tengah, 2022)
The Covid-19 pandemic situation has begun to decrease and the process of returning to normal situations has begun, although it cannot be in normal conditions as before, so that learning activities can be carried out face-to-face, and learning activities in schools will also be more effective. The purpose of this study was to determine the results of mathematics learning about the application of SPLDV in story problems to students of class X SMK Muhammadiyah Rembang. Data obtained from open class activities using face-to-face learning. The subjects to be studied are students of class X SMK Muhammadiyah Rembang. Data analysis was collected using Miles & Huberman's interactive analytical technique. The results obtained from the research are (1) Students can understand and observe story problems in daily life which are the application of SPLDV, (2) Students can change story questions into mathematical models and determine variable values or determine the completion of a story problems in SPLDV, (3) Students can understand the concept of story questions in the application of SPLDV so that learning objectives can be achieved, (4) With face- to-face learning, students appear to be more active in group discussions. (5) The presence of students is maximized by face-to-face learning. The application of the two-variable linear equation system (SPLDV) is very much in everyday life, with the application of the SPLDV the ability of students to think and understand a problem from story problems will be more developed.